Trephination of the Frontal Sinuses and Instillation of Clotrimazole Cream: A Computed Tomographic Study in Canine Cadavers1. Issue 3 (8th October 2015) - Burrow, Rachel; Baker, Martin; White, Lindsay; McConnell, James Fraser
Abstract: Objective: To use computed tomography (CT) to assess the distribution of surgically administered clotrimazole cream and associated filling of the frontal sinuses and caudal aspect of the nasal cavities in canine cadavers. Study Design: Observational study. Animals: Small (n = 1) and medium‐large (n = 11) breed canine cadavers. Methods: CT scans of 12 cadaveric canine heads were used to confirm absence of sinonasal disease. Then after creating an opening into the left and right frontal sinuses with a 3.2 mm Steinmann pin at standardized landmarks, clotrimazole cream (20 g) was instilled into each side. Postoperative CT scans of the heads was used to assess the distribution and degree of filling of the sinonasal cavities with clotrimazole cream, and to identify any damage to local structures. Results: Filling was excellent in 22 sinuses, very poor in 2, and excellent in all caudal nasal cavities. Two cadavers had damage: unilateral penetration of the cranium (2) and unilateral penetration of the lateral sinus wall (1). Conclusion: Excellent filling of most of the frontal sinuses and caudal nasal cavity of cadavers with clotrimazole cream is achieved when administered by this technique. Damage to local structures may occur intraoperatively using this technique.